Lutas por espaço e legitimidade na cidade: A inserção dos motoristas de aplicativos no ofício de transportar pessoas na cidade de Imperatriz/MA - PEREIRA, Ana Paula Pinto (2022)
The present work intends to explore the city of Imperatriz, Maranhão, from the experiences and representations of some of its subjects, the application drivers who work in the trade of transporting people. From this perspective, the research connects to reflections on the transformations and conflicts that the insertion of drivers through apps stimulated in the configuration of urban transport in the country (Elias, 2001) and in contemporary mobility and work relations. Focusing on the understanding of the transport configuration and the experiences and perceptions of its subjects in a medium-sized city in the southwest of Maranhão, the research was carried out through a multi-situated methodology, permeated by field stages and virtual moments. Developing a descriptive and analytical study, we sought to understand the experiences, identity representations and conflicts experienced by our interlocutors in their connections with the macrostructural aspects that involve the figuration of transport in the city of Imperatriz. In view of these objectives, as research results we can highlight our reflections on: the cyclical transformations of the transport configuration throughout the city's history; the weaving of new ways of being in the city, especially when we highlight mobility and the use of new technologies; the recurrence of conflicts around the subjects that make up the urban transport arrangement; and, the recent process of mobilization and organization of drivers by city apps, especially in times of Covid-19.